Genetics in breast cancer and treatment strategy : A current scenario - Islam, Muhammad (International Journal of Medicine, 2017)
This review aims to sketch the current scenario of breast cancer, which deals with the genetics, treatment strategy, drug resistance and over-comes as well as associated symptoms.